2002
DOI: 10.1089/107632702760240571
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Microbeads for Isolating and Growing Bone Marrow–Derived Progenitor Cells Capable of Forming Bone Tissue

Abstract: It has been demonstrated that bone marrow (BM)-derived pluripotent stem cells can be incorporated into muscle, bone, nerve, lung, stomach, intestine, and skin. Fibrin-based biodegradable microbeads (FMB) were developed for culturing, in suspension, a high density of cells, mostly of mesenchymal origin. In the current study, FMB were used to isolate and expand mesenchymal progenitor cells from BM of mice and rats. Cells from BM isolated on FMB (FMB-BM cells) were visualized by fluorescent confocal microscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 19 publications
0
56
0
Order By: Relevance
“…97 In a typical procedure, FMBs are synthesized by oil-stirring of a fibrinogen and thrombin mixture at 65°C-75°C for 6-8 hours and stored as a dry powder. 98 At this high temperature, fibrinogen denatures while factor XIIIa can remain active and cross-link proteins. Due to the conformational transformations of fibrinogen at these high temperatures, FMBs are highly haptotactic to various cell types, including osteogenic bone marrow-derived progenitors.…”
Section: Different Forms Of Fibrin Applications In Bone Tissue Enginementioning
confidence: 99%
See 1 more Smart Citation
“…97 In a typical procedure, FMBs are synthesized by oil-stirring of a fibrinogen and thrombin mixture at 65°C-75°C for 6-8 hours and stored as a dry powder. 98 At this high temperature, fibrinogen denatures while factor XIIIa can remain active and cross-link proteins. Due to the conformational transformations of fibrinogen at these high temperatures, FMBs are highly haptotactic to various cell types, including osteogenic bone marrow-derived progenitors.…”
Section: Different Forms Of Fibrin Applications In Bone Tissue Enginementioning
confidence: 99%
“…Due to the conformational transformations of fibrinogen at these high temperatures, FMBs are highly haptotactic to various cell types, including osteogenic bone marrow-derived progenitors. 99,100 For bone tissue engineering studies, the obtained FMBs were incubated for 2 days in a suspension containing whole 97,98,101 Next, authors cultured FMB-MSCs constructs in osteogenic medium and obtained a bone-like structure which was implanted into a mouse skull defect. After 2 months, results showed that defects filled with bone-like tissue had a Ca/P ratio similar to that of the native bone while no repair was seen in the control animals without implants or when the defect was filled with FMBs alone.…”
Section: Different Forms Of Fibrin Applications In Bone Tissue Enginementioning
confidence: 99%
“…30,32 It has been relatively rarely used for surface modification of scaffolds, with the exception of collagen-chitosan porous membranes, 31 or on electrospun poly(lactide-glycolide-caprolactone) nanofibers. 33 To the best of our knowledge, a combination of fibrin and ascorbic acid has not previously been used for constructing potential skin replacements, although this combination has been applied in tissue engineering of tendon and ligament, 34 cartilage, 35 bone, 36 smooth muscle, 37 and heart valves. 38 In these applications, ascorbic acid promoted appropriate differentiation and phenotypic maturation of cells and increased the collagen production in these cells.…”
mentioning
confidence: 99%
“…[21][22][23] It is a natural, biodegradable fibrous protein commonly used for clinical and experimental tissue engineering applications, 24 including surgical tissue adhesives, 25 delivery of growth factors, 26 genes, 27 and cells 28 as well as tissue engineering for cartilage, 29,30 skin, 31 and bone. [32][33][34] The deposition of fibrin at early time-points…”
Section: Introductionmentioning
confidence: 99%